Robert McFarlane interviewed by Hazel de Berg in the Hazel de Berg collection - McFarlane, Robert, 1942-; De Berg, Hazel, 1913-1984. (1980)
McFarlane speaks of his background and career as a photographer; working in photo-journalism; working in advertising; free lancing in Britain; going to Moscow and obtaining an interview with the ballet dancers Valerie and Galena Panov; the Panovs' eventual release from Russia. McFarlane speaks of his return to Australia and projects worked on; his views on the status of photography as a fine art in this country; the tradition of visual documentation; he explains his method of work.
Digital master available
Transcript available (40 p.)
Keywords: McFarlane, Robert, -- 1942- -- Interviews; Photographers -- Australia -- Interviews; Photojournalism